Processing of Individual Case Safety Reports in The Pharmacovigiland Department of Indonesian Vaccine Companies - Irham, Asep; Hasan Basri, Mursyid (Journal of World Science, 2023)
This study aimed to determine and analyze the processing design of individual case safety reports in Indonesia's pharmacovigilance department of vaccine companies. This study combines qualitative and quantitative studies that propose implementing the new artificial intelligence system for the PV Department. The results obtained from this study are problem-solving solutions by increasing the number of staff, using artificial intelligence (AI) technology in AEFI case processing to avoid errors and manual input, and approaching external stakeholders to be able to report safety data efficiently and more structured. With the addition of human resources to process the AEFI reporting data by one person, performance value will be increased to 165%. If the process utilizes AI technology, case processing performance increases to 219%. disruption of the performance of the pharmacovigilance department in Indonesian biopharmaceutical companies can be caused by the pandemic disrupting the way KIPI cases are reported, so the solution is the addition of human resources, changes in processes and SOPs, as well as approaches to external stakeholders to streamline case processing.